Introduction to the Special Issue on Moral Injury: Conceptual Challenges, Methodological Issues, and Clinical Applications. Issue 3 (4th June 2019) - Litz, Brett T.; Kerig, Patricia K.
Abstract: This article introduces a special issue of the Journal of Traumatic Stress devoted to new directions in the study of moral injury (MI), defined as transgressive harms and the outcomes of those experiences. Although a significant body of research has emerged devoted to the study of the MI construct, a number of conceptual and empirical challenges have arisen; these are summarized and discussed in the present article. In addition, this article proposes ways of overcoming these challenges in order to further research and clinical practice in the field. We then go on to introduce the content and themes of the present collection of articles in this special issue, all of which provide examples of some of the most innovative and forward‐looking work on the topic and expand into new conceptual frameworks, new methods of investigation, and new populations and contexts. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Introducción al número especial sobre daño moral: desafíos conceptuales, problemas metodológicos y aplicaciones clínicas INTRODUCCION AL NÚMERO ESPECIAL DE DAÑO MORAL Este artículo introduce el número especial de la Revista de Estrés Traumático (Journal of Traumatic Stress en su nombre en inglés) dedicado a nuevas direcciones en el estudio del daño moral (DM), definido como daños transgresores y los resultados de esas experiencias. Aunque surgió un importante cuerpo de investigación dedicado al estudio del constructo de DM, surgieron varios desafíos conceptuales y empíricos; Estos se resumen y discuten en el presente artículo. Además, este artículo propone formas de superar estos desafíos con el fin de promover la investigación y la práctica clínica en este campo. A continuación, presentamos el contenido y los temas de la presente colección de artículos en este especial temático, todos los cuales proporcionan ejemplos de algunos de los trabajos más innovadores y prospectivos sobre el tema y se expanden a nuevos marcos conceptuales, nuevos métodos de investigación y nuevas poblaciones y contextos. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Introduction to the Special Issue on Moral Injury: Conceptual Challenges, Methodological Issues, and Clinical Applications Traditional Chinese 標題: 道德創傷特刊簡介: 概念上的考驗、方法學問題和臨床應用 撮要: 本文為創傷壓力學術期刊特刊作簡介。此特刊專為探討道德創傷(MI)研究的新方向。MI的定義為犯法的傷害及經歷該等傷害所帶來的後果。雖然有顯著的研究數量檢視MI構念, 但亦出現了不少概念及實證方面的考驗。本文為解決這些問題提出方法, 使研究和臨床實踐能更進一步。我們將介紹此特刊收納的文章內容和主題, 它們均展示了此一研究範疇中最創新和具前瞻性的工作, 發展出新型的概念框架、新的探查方法, 以及檢視新的人口和環境類型。 Simplified Chinese 标题: 道德创伤特刊简介: 概念上的考验、方法学问题和临床应用 撮要: 本文为创伤压力学术期刊特刊作简介。此特刊专为探讨道德创伤(MI)研究的新方向。MI的定义为犯法的伤害及经历该等伤害所带来的后果。虽然有显著的研究数量检视MI构念, 但亦出现了不少概念及实证方面的考验。本文为解决这些问题提出方法, 使研究和临床实践能更进一步。我们将介绍此特刊收纳的文章内容和主题, 它们均展示了此一研究范畴中最创新和具前瞻性的工作, 发展出新型的概念框架、新的探查方法, 以及检视新的人口和环境类型。